Parents’ Perception: Early Childhood Social Behaviour During Physical Distancing in the Covid-19 Pandemic - Ekyana, Luluk; Fauziddin, Mohammad; Arifiyanti, Nurul (Program Studi Magister Pendidikan Anak Usia Dini, 2021)
During physical distancing, children do not meet their peers to play or talk together. Peer relationships have a crucial influence on all child development, especially for social skills or behaviour during early childhood. This study aims to determine changes in children's social behaviour during physical distancing during the Covid-19 pandemic. This research method is a descriptive quantitative study designed with the percentage value was used as a score for measuring the results of parental observations of children concerning the child's social behaviour instrument. Quota sampling (150 parents) was used to reach participants from various cities in Indonesia to see cultural differences. Data on children's social behaviour was obtained using the Preschool and Kindergarten Behaviour Scale (PKBS) tests. The data were then analysed using descriptive statistics. The results show that there are changes in children's social behaviour during physical distancing. Children who are less independent (58.9%) are the biggest decline in social behaviour reported by parents, while the one who changes the least is cleaning up the mess that has been made (38.7%). The implication of the results of this study is that parents should continue to pay attention to their children's social behaviour by providing opportunities for children to interact with peers in the house while still paying attention to health protocols. Keywords: Early Childhood, Social Behaviour, Physical Distancing References: Aksoy, P., & Baran, G. (2010). Review of studies aimed at bringing social skills for children in preschool period. Procedia - Social and Behavioural Sciences, 9, 663–669. https://doi.org/10.1016/j.sbspro.2010.12.214 Al-Tammemi, A. B. (2020). The Battle Against COVID-19 in Jordan: An Early Overview of the Jordanian Experience. Frontiers in Public Health, 8(May), 1–6. https://doi.org/10.3389/fpubh.2020.00188 Arkorful, V., & Abaidoo, N. (2015). The role of e-learning, advantages, and disadvantages of its adoption in higher education. International Journal of Instructional Technology and Distance Learning, 12(1), 29–42. Atiles, J. T., Almodóvar, M., Chavarría Vargas, A., Dias, M. J. A., & Zúñiga León, I. M. (2021). International responses to COVID-19: Challenges faced by early childhood professionals. European Early Childhood Education Research Journal, 29(1), 66–78. https://doi.org/10.1080/1350293X.2021.1872674 Baloran, E. T. (2020). Knowledge, Attitudes, Anxiety, and Coping Strategies of Students during COVID-19 Pandemic. Journal of Loss and Trauma, 25(8), 635–642. https://doi.org/10.1080/15325024.2020.1769300 Berns, R. M. (2007). Child, Family, School, and Community. Cengage. Brooks, S. K., Webster, R. K., Smith, L. E., Woodland, L., Wessely, S., Greenberg, N., & Rubin, G. J. (2020). The psychological impact of quarantine and how to reduce it: Rapid review of the evidence. The Lancet, 395(10227), 912–920. https://doi.org/10.1016/S0140-6736(20)30460-8 Cachón-Zagalaz, J., Zagalaz-Sánchez, M. L., Arufe-Giráldez, V., Sanmiguel-Rodríguez, A., & González-Valero, G. (2021). Physical activity and daily routine among children aged 0-12 during the COVID-19 pandemic in Spain. International Journal of Environmental Research and Public Health, 18(2), 1–13. https://doi.org/10.3390/ijerph18020703 Ceylan, S. S., Erdoğan, Ç., & Turan, T. (2021). Investigation of the effects of restrictions applied on children during Covid-19 pandemic. Journal of Pediatric Nursing, 61, 340–345. https://doi.org/10.1016/j.pedn.2021.09.013 Chaelin, K. R. et al. (2018). Association of Digital Media Use with Subsequent Symptoms of Attention Defi-cit/Hyperactivity Disorder Among Adolescents. J. Am. Med. Assoc. Corredor, G. A., Justicia-Arráez, A., Romero-López, M., & Benavides-Nieto, A. (2017). Longitudinal Study of the Effects of Social Competence on Behavioral Problems. Procedia - Social and Behavioral Sciences, 237(June 2016), 479–485. https://doi.org/10.1016/j.sbspro.2017.02.093 de Figueiredo, C. S., Sandre, P. C., Portugal, L. C. L., Mázala-de-Oliveira, T., da Silva Chagas, L., Raony, Í., Ferreira, E. S., Giestal-de-Araujo, E., dos Santos, A. A., & Bomfim, P. O. S. (2021). COVID-19 pandemic impact on children and adolescents’ mental health: Biological, environmental, and social factors. Progress in Neuro-Psychopharmacology and Biological Psychiatry, 106(November 2020). https://doi.org/10.1016/j.pnpbp.2020.110171 Diesendruck, G., & Ben-Eliyahu, A. (2006). The relationships among social cognition, peer acceptance, and social behavior in Israeli kindergarteners. International Journal of Behavioral Development, 30(2), 137–147. https://doi.org/10.1177/0165025406063628 Dong, C., Cao, S., & Li, H. (2020). Young children’s online learning during COVID-19 pandemic: Chinese parents’ beliefs and attitudes. Children and Youth Services Review, 118(September), 105440. https://doi.org/10.1016/j.childyouth.2020.105440 Gay, L. R., Mills, G. E., & Airasian, P. W. (2012). Educational research: Competencies for analysis and applications(10th ed). Pearson. Gelir, I., & Duzen, N. (2021). Children’s changing behaviours and routines, challenges, and opportunities for parents during the COVID-19 pandemic. Education 3-13, 0(0), 1–11. https://doi.org/10.1080/03004279.2021.1921822 Goldschmidt, K. (2020). The COVID-19 Pandemic: Technology use to Support the Wellbeing of Children. Journal of Pediatric Nursing, 53(xxxx), 88–90. https://doi.org/10.1016/j.pedn.2020.04.013 Goodman, A., Joshi, H., & Nasim, B. (2015). Social and emotional skills in childhood and their long-term effects on adult life. A Review for The Eraly Intervention Foundation, March, 118. Grier, L. K., & Boutakidis, I. (2018). The ecology of social support in relation to academic and behavioral self-perceptions among African American boys and girls. Journal of Human Behaviour in The Social Environment, 28(6), 798–816. Gülay, H., & Önder, A. (2013). A study of social-emotional adjustment levels of preschool children in relation to peer relationships. Education 3-13, 41(5), 514–522. https://doi.org/10.1080/03004279.2011.609827 Hu, B. Y., Johnson, G. K., Teo, T., & Wu, Z. (2020). Relationship Between Screen Time and Chinese Children’s Cognitive and Social Development. Journal of Research in Childhood Education, 34(2), 183–207. https://doi.org/10.1080/02568543.2019.1702600 Idoiaga Mondragon, N., Berasategi Sancho, N., Dosil Santamaria, M., & Eiguren Munitis, A. (2021). Struggling to breathe: A qualitative study of children’s wellbeing during lockdown in Spain. Psychology and Health, 36(2), 179–194. https://doi.org/10.1080/08870446.2020.1804570 Izza, H. (2020). Meningkatkan Perkembangan Sosial Anak Usia Dini melalui Metode Proyek. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 4(2), 951. https://doi.org/10.31004/obsesi.v4i2.483 Koh, W. C., Naing, L., & Wong, J. (2020). Estimating the impact of physical distancing measures in containing COVID-19: An empirical analysis. International Journal of Infectious Diseases, 100, 42–49. https://doi.org/10.1016/j.ijid.2020.08.026 Kusuma, L., Dimyati, & Harun. (2022). Perhatian Orang tua dalam Mendukung Keterampilan Sosial Anak selama Pandemi Covid-19. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 6(1), 473–491. https://doi.org/10.31004/obsesi.v6i1.959 Kyriazis, A., Mews, G., Belpaire, E., Aerts, J., & Malik, S. A. (2020). Physical distancing, children, and urban health. Cities & Health, 00(00), 1–6. https://doi.org/10.1080/23748834.2020.1809787 Lau, E. Y. H., & Lee, K. (2020). Parents’ Views on Young Children’s Distance Learning and Screen Time During COVID-19 Class Suspension in Hong Kong. Early Education and Development, 00(00), 1–18. https://doi.org/10.1080/10409289.2020.1843925 Leeuw, R. A. De, Logger, D. N., Westerman, M., Bretschneider, J., Plomp, M., & Scheele, F. (2019). Influencing factors in the implementation of postgraduate medical e-learning: A thematic analysis. 1–10. Liu, Y., Yue, S., Hu, X., Zhu, J., Wu, Z., Wang, J., & Wu, Y. (2021). Associations between feelings/behaviors during COVID-19 pandemic lockdown and depression/anxiety after lockdown in a sample of Chinese children and adolescents. Journal of Affective Disorders, 284(November 2020), 98–103. https://doi.org/10.1016/j.jad.2021.02.001 Mantovani, S., Bove, C., Ferri, P., Manzoni, P., Cesa Bianchi, A., & Picca, M. (2021). Children ‘under lockdown’: Voices, experiences, and resources during and after the COVID-19 emergency. Insights from a survey with children and families in the Lombardy region of Italy. European Early Childhood Education Research Journal, 29(1), 35–50. https://doi.org/10.1080/1350293X.2021.1872673 McCormack, G. R., Doyle-Baker, P. K., Petersen, J. A., & Ghoneim, D. (2020). Parent anxiety and perceptions of their child’s physical activity and sedentary behaviour during the COVID-19 pandemic in Canada. Preventive Medicine Reports, 20, 101275. https://doi.org/10.1016/j.pmedr.2020.101275 Melinda, A. E., & Izzati. (2014). Perkembangan Sosial Anak Usia Dini. Jurnal Pendidikan Anak Usia Dini Undiksha, 9(1), 127–131. Merell, K. W. (2013). Prechool and kindergarten behavior scales. In Journal of Chemical Information and Modeling(Vol. 53, Issue 9). Merkaš, M., Perić, K., & Žulec, A. (2021). Parent Distraction with Technology and Child Social Competence during the COVID-19 Pandemic: The Role of Parental Emotional Stability. Journal of Family Communication, 21(3), 186–204. https://doi.org/10.1080/15267431.2021.1931228 Mochida, S., Sanada, M., Shao, Q., Lee, J., Takaoka, J., Ando, S., & Sakakihara, Y. (2021). Factors modifying children’s stress during the COVID-19 pandemic in Japan. European Early Childhood Education Research Journal. https://doi.org/10.1080/1350293X.2021.1872669 Mohamed, A. H. H. (2017). Gender as a moderator of the association between teacher – child relationship and social skills in preschool. Early Child Development and Care, 0(0), 1–15. https://doi.org/10.1080/03004430.2016.1278371 Morelli, M., Cattelino, E., Baiocco, R., Trumello, C., Babore, A., Candelori, C., & Chirumbolo, A. (2020). Parents and Children During the COVID-19 Lockdown: The Influence of Parenting Distress and Parenting Self-Efficacy on Children’s Emotional Well-Being. Frontiers in Psychology, 11(October), 1–10. https://doi.org/10.3389/fpsyg.2020.584645 Morgül, E., Kallitsoglou, A., & Essau, C. (2020). Psychological effects of the COVID-19 lockdown on children and families in the UK. Revista de Psicología Clínica Con Niños y Adolescentes, 7(3), 42–48. https://doi.org/10.21134/rpcna.2020.mon.2049 Munasinghe, S., Sperandei, S., Freebairn, L., Conroy, E., Jani, H., Marjanovic, S., & Page, A. (2020). The Impact of Physical Distancing Policies During the COVID-19 Pandemic on Health and Well-Being Among Australian Adolescents. Journal of Adolescent Health, 67(5), 653–661. https://doi.org/10.1016/j.jadohealth.2020.08.008 Munastiwi, E., & Puryono, S. (2021). Unprepared management decreases education performance in kindergartens during Covid-19 pandemic. Heliyon, 7(5), e07138. https://doi.org/10.1016/j.heliyon.2021.e07138 Naser, A. Y., Al-Hadithi, H. T., Dahmash, E. Z., Alwafi, H., Alwan, S. S., & Abdullah, Z. A. (2020). The effect of the 2019 coronavirus disease outbreak on social relationships: A cross-sectional study in Jordan. International Journal of Social Psychiatry. https://doi.org/10.1177/0020764020966631 Nofziger, S. (2008). The “Cause” of Low Self-Control. Journal Research in Crime and Delinquency, 45(2), 191–224. O’Keeffe, C., & McNally, S. (2021). ‘Uncharted territory’: Teachers’ perspectives on play in early childhood classrooms in Ireland during the pandemic. European Early Childhood Education Research Journal, 29(1), 79–95. https://doi.org/10.1080/1350293X.2021.1872668 Ozturk Eyimaya, A., & Yalçin Irmak, A. (2021). Relationship between parenting practices and children’s screen time during the COVID-19 Pandemic in Turkey. Journal of Pediatric Nursing, 56, 24–29. https://doi.org/10.1016/j.pedn.2020.10.002 Parczewska, T. (2020). Difficult situations and ways of coping with them in the experiences of parents homeschooling their children during the COVID-19 pandemic in Poland. Education 3-13, 0(0), 1–12. https://doi.org/10.1080/03004279.2020.1812689 Pascal, C., & Bertram, T. (2021). What do young children have to say? Recognising their voices, wisdom, agency and need for companionship during the COVID pandemic. European Early Childhood Education Research Journal, 20–34. https://doi.org/10.1080/1350293X.2021.1872676 Popyk, A. (2020). The impact of distance learning on the social practices of schoolchildren during the COVID-19 pandemic: Reconstructing values of migrant children in Poland. European Societies, 0(0), 1–15. https://doi.org/10.1080/14616696.2020.1831038 Quennerstedt, A. (2016). Young children’s enactments of human rights in early childhood education. International Journal of Early Years Education, 24(1), 5–18. https://doi.org/10.1080/09669760.2015.1096238 Rachman, S. P. D., & Cahyani, I. (2019). Perkembangan Keterampilan Sosial Anak Usia Dini. (JAPRA) Jurnal Pendidikan Raudhatul Athfal (JAPRA), 2(1), 52–65. https://doi.org/10.15575/japra.v2i1.5312 Ramadhani, P. R., & Fauziah, P. Y. (2020). Hubungan Sebaya dan Permainan Tradisional pada Keterampilan Sosial dan Emosional Anak Usia Dini Abstrak. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 4(2), 1011–1020. https://doi.org/10.31004/obsesi.v4i2.502 Ren, L., Hu, B. Y., & Song, Z. (2019). Child routines mediate the relationship between parenting and social-emotional development in Chinese children. Children and Youth Services Review, 98(December 2018), 1–9. https://doi.org/10.1016/j.childyouth.2018.12.016 Ren, L., & Xu, W. (2019). Coparenting and Chinese preschoolers’ social-emotional development: Child routines as a mediator. Children and Youth Services Review, 107, 104549. https://doi.org/10.1016/j.childyouth.2019.104549 Rusmayadi, & Herman. (2019). The Effect of Social Skill on Children’s Independence. Journal of Educational Science and Technology, 5(2), 159–165. Sari, C. R., Hartati, S., & Yetti, E. (2019). Peningkatan Perilaku Sosial Anak melalui Permainan Tradisional Sumatera Barat. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 3(2), 416–424. https://doi.org/10.31004/obsesi.v3i2.225 Sendil, C. O., & Erden, F. T. (2012). Preschool Teachers’ Strategies to Enhance Social Interaction Skills of Children during Playtime. Procedia - Social and Behavioral Sciences, 47, 918–923. https://doi.org/10.1016/j.sbspro.2012.06.757 Setiawati, E., Solihatulmillah, E., Cahyono, H., & Dewi, A. (2019). The Effect of Gadget on Children’s Social Capability. Journal of Physics: Conference Series, 1179(1). https://doi.org/10.1088/1742-6596/1179/1/012113 Setyawan, C. F., Sudirman, D. F., Sari, D. P., Rizki, F., Eva, N., Psi, S., & Psi, M. (2021). Asesmen Perkembangan Sosio Emosinal pada Anak Usia Dini. Prosiding Seminar Nasional Dan Call Paper Mahasiswa “Memperkuat Kontribusi Kesehatan Mental Dalam Penyelesaian Pandemi Covid 19: Tinjauan Multidisipliner”, April, 58–70. Sheridan, S. M., Knoche, L. L., Boise, C., Witte, A., Koziol, N., Prokasky, A., Schumacher, R., & Kerby, H. (2021). Relationships as Malleable Factors for Children’s Social-Behavioral Skills from Preschool to Grade 1: A Longitudinal Analysis. Early Education and Development, 00(00), 1–21. https://doi.org/10.1080/10409289.2021.1936374 Siekkinen, M., Pakarinen, E., Lerkkanen, M., Poikkeus, A., Salminen, J., Poskiparta, E., & Nurmi, E. (2014). Early Education and Development Social Competence Among 6-year-old Children and Classroom Instructional Support and Teacher Stress. Early Education and Development, 24(6), 877–897. https://doi.org/10.1080/10409289.2013.745183 Sintia, N., Kuswanto, C. W., & Meriyati, M. (2019). Meningkatkan Kemampuan Sosial Anak Usia Dini dengan Model Outbound. Jurnal CARE (Children Advisory Research and Education), 6(2), 1–10. Siregar, S. L., & Subiyantoro. (2021). Peran Orang Tua dalam Mengembangkan Kemampuan Sosial Emosioal Anak Usia Dini. EDUKIDS: Jurnal Pertumbuhan, Perkembangan, Dan Pendidikan Anak Usia Dini, 18(1), 1–6. https://doi.org/10.17509/edukids.v18i1.31828 Stephen, C., & Edwards, S. (2018). Young Children Playing and Learning in a Digital Age. Routledge. Tchimtchoua Tamo, A. R. (2020). An analysis of mother stress before and during COVID-19 pandemic: The case of China. Health Care for Women International, 41(11–12), 1–14. https://doi.org/10.1080/07399332.2020.1841194 Unnever, J. D., Cullen, F. T., & Agnew, R. (2006). Why is “Bad” Parenting Criminogenic? Implications From Rival Theories. Youth Violence and Juvenile Justice, 4(1), 3–33. https://doi.org/10.1177/1541204005282310 Wang, S., Hu, B. Y., LoCasale-Crouch, J., & Li, J. (2021). Supportive parenting and social and behavioral development: Do classroom emotional support moderate? Journal of Applied Developmental Psychology, 77(101331). Zhang, X. (2021). Barriers and benefits of primary caregivers’ involvement in children’s education during COVID-19 school closures. International Journal of Disaster Risk Reduction, 66(December 2020), 102570. https://doi.org/10.1016/j.ijdrr.2021.102570 Zhang, X., & Nurmi, J. E. (2012). Teacher-child relationships and social competence: A two-year longitudinal study of Chinese preschoolers. Journal of Applied Developmental Psychology, 33(3), 125–135. https://doi.org/10.1016/j.appdev.2012.03.001